2021
DOI: 10.3389/fimmu.2021.684344
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Modulates the LPS- and Aβ-Induced Neuroinflammatory Response in Cells, Wild-Type Mice, and 5xFAD Mice

Abstract: Sorafenib is FDA-approved for the treatment of primary kidney or liver cancer, but its ability to inhibit many types of kinases suggests it may have potential for treating other diseases. Here, the effects of sorafenib on neuroinflammatory responses in vitro and in vivo and the underlying mechanisms were assessed. Sorafenib reduced the induction of mRNA levels of the proinflammatory cytokines COX-2 and IL-1β by LPS in BV2 microglial cells, but in primary astrocytes, only COX-2 mRNA levels were altered by soraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…TLR subfamily 4 (TLR4) is activated by pathogenic molecules such as LPS. Several studies have reported that drugs that reduce proinflammatory cytokine levels in vitro and in vivo via TLR4-dependent signaling pathways hold potential for treating neuroinflammation-linked neurodegenerative diseases [ 20 , 21 , 36 , 37 ]. For instance, MAO inhibitor treatment significantly reduces the LPS-induced increase in IL-1β and IL-6 mRNA levels, and IL-6 but not IL-1β levels are partially dependent on TLR4 signaling in BV2 microglial cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TLR subfamily 4 (TLR4) is activated by pathogenic molecules such as LPS. Several studies have reported that drugs that reduce proinflammatory cytokine levels in vitro and in vivo via TLR4-dependent signaling pathways hold potential for treating neuroinflammation-linked neurodegenerative diseases [ 20 , 21 , 36 , 37 ]. For instance, MAO inhibitor treatment significantly reduces the LPS-induced increase in IL-1β and IL-6 mRNA levels, and IL-6 but not IL-1β levels are partially dependent on TLR4 signaling in BV2 microglial cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MAO inhibitor treatment significantly reduces the LPS-induced increase in IL-1β and IL-6 mRNA levels, and IL-6 but not IL-1β levels are partially dependent on TLR4 signaling in BV2 microglial cells [ 37 ]. In addition, the VEGFR antagonist sorafenib and ATP-sensitive potassium channel blocker gliquidone reduce proinflammatory cytokine levels in BV2 microglia cells via TLR4-linked signaling pathways [ 21 , 36 ]. In this study, treatment of BV2 microglial cells with LPS, TLR4 inhibitor, and nilotinib significantly downregulated LPS-evoked IL-1β levels compared with treatment with LPS and TLR4 inhibitor but not treatment with LPS and nilotinib, indicating that the effects of nilotinib on IL-1β levels are independent of TLR4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly however, some of the drugs predicted to have a concordant signature with AD have previously been shown to be able to ameliorate the AD condition, as is the case for sorafenib [ 45 ] and montelukast [ 46 ]. Although this observation requires careful attention and validation in the in vivo setting, we may hypothesize that the pathways targeted by these drugs, rather than being pathological, may instead represent compensatory responses to the concomitant aberrant processes associated with the presence of fAD mutations.…”
Section: Discussionmentioning
confidence: 99%